1996
DOI: 10.1073/pnas.93.13.6499
|View full text |Cite
|
Sign up to set email alerts
|

Chemical basis of courtship in a beetle (Neopyrochroa flabellata): Cantharidin as "nuptial gift".

Abstract: The amount of cantharidin (Spanish fly) that the Neopyrochroaflabellata male presents to the female as a glandular offering during courtship represents only a small fraction of the total cantharidin the male accumulates systemically following ingestion of the compound. A major fraction of the acquired cantharidin is stored by the male in the large accessory glands of the reproductive system. At mating, the male transfers this supply, presumably as part of the sperm package, to the spermatheca of the female. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 17 publications
(22 reference statements)
1
51
0
Order By: Relevance
“…The variation in female investment of melatonin may also explain the lack of observed variation in fecundity in the current experiment, as females were mated to males that were maintained under normal light conditions. Thus it is conceivable that male-derived melatonin transferred during mating was able to mitigate variation in female condition during egg-laying sensu the distasteful cantharidins transferred during mating by the male beetle, Neopyrochroa flabellate, which females then allocate to eggs, so providing them with protection from predation [96]. The fact that the effect of melatonin supplementation on immune function varied highlights the complexity of the underlying relationships between light, melatonin and life history traits.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in female investment of melatonin may also explain the lack of observed variation in fecundity in the current experiment, as females were mated to males that were maintained under normal light conditions. Thus it is conceivable that male-derived melatonin transferred during mating was able to mitigate variation in female condition during egg-laying sensu the distasteful cantharidins transferred during mating by the male beetle, Neopyrochroa flabellate, which females then allocate to eggs, so providing them with protection from predation [96]. The fact that the effect of melatonin supplementation on immune function varied highlights the complexity of the underlying relationships between light, melatonin and life history traits.…”
Section: Discussionmentioning
confidence: 99%
“…We predict, however, that the strategy will be shown to have counterparts in insects, where males so often transmit sizeable spermatophores to females (21). One can certainly imagine the strategy being at play in such insects as D. gilipus and N. flabellata, where seminal transfer of defensive chemicals has been established (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…We ourselves had shown such chemical transfer to occur in a danaid butterfly, Danaus gilippus, where the male, as in Utetheisa, transmits PA that it sequesters from plants to the female (15), and in a pyrochroid beetle, Neopyrochroa flabellata, where the terpenoid toxin cantharidin is bestowed on the female (16,17). In all these cases, including Utetheisa, the assumption had been that the beneficiaries of the transfer are the offspring, and evidence did indeed indicate that the eggs of Utetheisa and N. flabellata derive protection from the PA or cantharidin they receive from their respective fathers (5, 17).…”
Section: Discussionmentioning
confidence: 99%
“…The focus of this study is the feeding ecology of parents in the context of defensive provisioning. Natural selection may favour those females that actively accumulate and endow their offspring with more defensive chemicals when the concentration has an effect on offspring survival [3,[7][8][9]. Although a study has reported mating-induced behavioural switching in females of a firefly, which is likely to facilitate acquisition of toxins used for chemical protection of offspring [14], few studies have addressed natural behaviour related to acquisition of defensive chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…In certain groups of insects, the mechanism and ecology of chemical protection of offspring have received much attention (e.g. [3,[7][8][9]), but there is comparatively little research on vertebrate systems, even though examples of vertebrate species that produce unpalatable or poisonous offspring are increasing [4,6,10].…”
Section: Introductionmentioning
confidence: 99%